Clinical and functional characterization of a novel TNFRSF9 variant causing immune dysregulation with predisposition to EBV-driven lymphomagenesis - Zhao, Peiwei; Chen, Kailan; Yang, Li; Wan, Chunhui; Zhang, Lei; Luo, Sukun; He, Xuelian (Frontiers in Immunology, 2025)
IntroductionThe TNFRSF9 gene encodes the costimulatory receptor CD137, also known as 4-1BB, which plays a critical role in sustaining effective cytotoxic T-cell responses. Variants in the TNFRSF9 gene are associated with an extremely rare autosomal recessive primary immunodeficiency disorder characterized by recurrent sinopulmonary infections and EBV-induced lymphoproliferation.MethodsWe report a case siblings exhibiting EBV viremia, recurrent respiratory infections, and Burkitt lymphoma. Whole-exome sequencing (WES) was performed. Sanger sequencing was used to validate the variants. In vitro functional study was performed by western blot, flow cytometry assays and luciferase assays.ResultsGenetic analysis identified a novel missense variant in the TNFRSF9 gene (NM_001561.5: c.359G>C, p.C120S). Functional analysis in vitro demonstrated that this variant decreased the expression of TNFRSF9 both mRNA and protein levels. Western blot analysis revealed a significant decrease in phosphorylated-AKT. Luciferase assays showed that the p.C120S variant diminished the activity of the NF-κB pathway. Immunophenotyping of the patient’s peripheral blood revealed a significant reduction in CD27+ memory B cells, which are critical for long-term humoral immunity. Additionally, there was a notable decrease in IFN-γ secretion in CD8+ T cells, suggesting impaired cytotoxic T-cell function. These findings align with the clinical presentation of immunodeficiency and lymphoproliferation observed in the patients. We also reviewed 9 previously reported patients with homozygous or compound heterozygous TNFRSF9 variants. The clinical manifestations among these patients were highly heterogeneous, ranging from asymptomatic to malignancies.DiscussionIn summary, we identified a novel TNFRSF9 variant associated with immunodeficiency and lymphoproliferation, supported by functional evidence demonstrating its impact on gene expression, AKT and NF-κB signaling pathways, and immune cell function. Our findings expand the mutation spectrum of the TNFRSF9 gene and provide new insights into the molecular mechanisms underlying this rare immunodeficiency disorder.